IMPLICATION OF MINI PROJECT ORGANIC CHEMISTRY EXPERIMENTS FOR IMPROVING ORGANIC CHEMISTRY CONCEPT - Sri Mulyanti; Atik Rahmawati; Ulfa Lutfianasari (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2021)
IMPLICATION OF MINI PROJECT ORGANIC CHEMISTRY EXPERIMENTS FOR IMPROVING ORGANIC CHEMISTRY CONCEPTAbstractOrganic Chemistry Practice is one of the courses in the chemical education department that must be taken by pre-service teacher of chemistry, still lack of mastery of students on organic chemistry concepts, requiring lecturers to be able to design the experiment in such a way so as to increase mastery of the concept of organic chemistry students in Organic Chemistry Practice. This study aims to apply the mini project model to the Organic Chemistry Practice so that it is expected to increase students' mastery of concepts in organic chemistry. The research was conducted using quantitative methods, its measuring conceptual change from the students from N-gain score. The results showed that there was an increase in students' mastery of concepts based on the% N-gain obtained. The majority of students are at a high criterion with% N-Gain> 70. The t test shows the significance of the implementation of the mini project model to increase students' mastery of concept concepts.AbstrakRendahnya penguasaan mahasiswa terhadap konsep-konsep kimia organik, menuntut pengajar untuk dapat mendesain praktikum sedemikian rupa, sehingga dapat meningkatkan penguasaan konsep kimia organik mahasiswa pada Praktikum Kimia Organik. Penelitian ini bertujuan untuk menerapkan model mini project pada Praktikum Kimia Organik sehingga diharapkan dapat meningkatkan penguasaan konsep mahasiswa pada materi kimia organik. Penelitian dilakukan dengan metode kuantitatif, yakni mengukur hasil tes penguasaan konsep mahasiswa. Hasil penelitian menunjukkan bahwa terjadi peningkatan penguasaan konsep mahasiswa berdasarkan hasil %N-Gain yang diperoleh. Mayoritas mahasiswa berada pada kriteria tinggi dengan %N-Gain > dari 70. Uji t menunjukkan signifikansi pelaksanaan model mini project terhadap peningkatan penguasaan konsep mahasiswa.